KEHADIRAN, KESABARAN, KETEKUNAN MISI DALAM SEBUAH PUSAT PERDAGANGAN MANUSIA - John Mansford Prior (Institut Filsafat dan Teknologi Kreatif Ledalero, 2014)
This essay looks at human trafficking as the underbelly of an unregulated global economy. Using data collated by the UN and studies undertaken by independent research institutes, the global pattern of trafficking is outlined before focusing on Southeast Asia, a key hub in this modern form of slavery. Key characteristics and motivations are delineated with reference to UN definitions and legislation in Southeast Asia. Attention is given to the global need for cheap labour, sex workers and the widespread trafficking of children. Then, the phenomenon is seen through the eyes of faith drawing on four key biblical attitudes: upholding human dignity (protection), reaching to the heart (prevention), naming the sin (prosecution), and extending Gospel community (partnering). Kata-kata Kunci: Ekonomi global, perdagangan manusia, perdagangan perempuan dan anak-anak, undang-undang Asia Tenggara, perlindungan, pencegahan, jaringan berbasis iman.